2016
DOI: 10.1155/2016/3596261
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Otitis Media in Korea, 2012: A Nationally Representative Cross-Sectional Study

Abstract: Background. Otitis media (OM) is a common communicable disease that is associated with a substantial economic burden. However, no Korean studies have evaluated OM-related trends after the introduction of the pneumococcal conjugate vaccines. Purpose. This study aimed to estimate the prevalence and economic burden of OM in Korea using nationally representative data. Methods. The burden of OM was estimated nationally representative data such as national health insurance claims data from 2012, based on the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“… 13 In Korea, a nationally representative cross-sectional study evaluated the economic burden of otitis media in 2012 reported the total cost of otitis media in 0–9 year age group as 257.87 million Dollars in the outpatient setting. 14 Since there are differences in health policies as well as in national economies of the countries, these results are not comparable.…”
Section: Discussionmentioning
confidence: 97%
“… 13 In Korea, a nationally representative cross-sectional study evaluated the economic burden of otitis media in 2012 reported the total cost of otitis media in 0–9 year age group as 257.87 million Dollars in the outpatient setting. 14 Since there are differences in health policies as well as in national economies of the countries, these results are not comparable.…”
Section: Discussionmentioning
confidence: 97%
“…Medical costs for each of the 238 diseases were calculated based on the definitions of prevalence for each disease. As determined by a literature review and expert consultation, patients for each disease were defined as those who were hospitalized for the major illness at least once or were treated as an outpatient at least 1–5 times 8910…”
Section: Methodsmentioning
confidence: 99%
“…Despite the importance of measuring the socioeconomic burden, previous Korean studies attempting to estimate socioeconomic burden have generally been conducted for a single disease or group of diseases 8910. For example, in 2009, one study computed economic burden caused by cancers 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 10 11 Previous studies have determined the economic burden of diseases in Korea by measuring the direct medical costs of inpatient and outpatient care, pharmaceuticals, direct non-medical costs (e.g., transportation costs and caregiver expenses), and indirect costs owing to productivity loss regarding morbidity and mortality. 12 13 14 15 16 17 Notwithstanding, despite the aforementioned importance of transportation in healthcare utilization, no previous Korean study has independently investigated transportation cost burden.…”
Section: Introductionmentioning
confidence: 99%